Activity test of antibody recombinant specificity Escherichia coli O157:H7 - Hiep, Hoang Phu; Kim Xuan, Le Thi; Lua, Nguyen Minh; Minh Huyen, Nguyen Thi; Ha, Tran Manh; Duc, Dao Minh; Nhi, Nguyen Bich; Huan, Le Quang (Academia Journal of Biology, 2015)
Antibodies are immunoglobulin molecules which originally are glycoprotein that play role to identify and neutralize foreign agents such as viruses or bacteria. In this study, antibody protein recombine specificity of E. coli O157:H7 which was purified using hybrid methods. Next, antibody activity was tested by the methods as Dot Blot, Western Blot & ELISA. The results showed thatantibody protein specificly paired with E. coli O157:H7. Initially determine the specificity of antibodies by recombinant methods silica nanoparticles attached to antibodies and staining with E. coli O157:H7 and examined under a microscope. Thereby creating a scientific basis for the study of microbial diagnostic kit created in food samples as well as providing additional sources of antibody therapy of poisoning caused by bacteria E. coli O157:H7.